to educational counselors' cognitive controls build and apply)) (Journal of the College of Basic Education, 2022)
The concept of cognitive control from the point of view of the social system refers to the various forces that society exercises to influence its members to use them to protect its constituents and preserve its values ​​and specifications, and to resist the factors of deviation and manifestations of disobedience and rebellion. Individuals and groups of society accept the prevailing system, and when the cognitive control system suffers defects and weaknesses, it is reflected on social life in its various aspects (Al-Akhras, 1997, p. 12). The era in which man lives is characterized by rapid development and amazing progress in various fields (educational, political, economic, and informational), and with the increase in scientific progress and the expansion of life demands, the need for people to control their thoughts, behavior and actions has increased, as cognitive control is one of the basic concepts in the formation of personality. Which has importance in the individual’s ability to direct and organize himself and to modify aspects of his behavior, thoughts, emotions, and tendencies, that is, its influence extends to various dimensions of personality if many inappropriate actions can be controlled (Habib, 1997: 50). Search objective : Building a The level of cognitive controls of educational counselors.Identifying The level of cognitive controls of educational counselors. The researcher built a scale of measure cognitive controls of the educational counselors’cognitive controls of the research sample, where the scale consisted of (30) paragraphs formulated in the manner of verbal attitudes, each of which represents a hypothetical situation with two alternatives to the answer, one of which measures the cognitive control and the other does not measure it, and the researcher gave the two attitudes degrees (2,1) Thus, and extracted the psychometric properties of honesty (discriminative power, internal homogeneity and stability by re-test method, the (Alpha-Cronbach) equation and the statistical indicators of the scale, and verifying the second objective using T-test for one sample.The research reached the following results:The educational counselors have a high degree of cognitive control.To complement the current research, the researcher presented a number of recommendations and suggestions.Benefit from the scale of the current research that was prepared by the researcher for the Directorate of Psychological Guidance and Educational Guidance in all the General Directorates of Education in order to develop and improve its work according to the level of the two variable.